Optical Absorption of Impurities and Defects in Semiconducting Crystals Electronic Absorption of Deep Centres and Vibrational Spectra - Pajot, Bernard; Clerjaud, Bernard; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book outlines, with the help of several specific examples, the important role played by absorption spectroscopy in the investigation of deep-level centers introduced in semiconductors and insulators like diamond, silicon, germanium and gallium arsenide by high-energy irradiation, residual impurities, and defects produced during crystal growth. It also describes the crucial role played by vibrational spectroscopy to determine the atomic structure and symmetry of complexes associated with light impurities like hydrogen, carbon, nitrogen and oxygen, and as a tool for quantitative analysis of these elements in the materials.
Foreword -- Preface -- Notations and symbols -- Introduction -- Bulk optical absorption -- Instrumental methods for absorption spectroscopy -- Absorption of deep centres and bound excitons -- Vibrational absorption of substitutional atoms and related centres -- Vibrational absorption of interstitial atoms and related centres -- Vibrational absorption III -- Quasi substitutional atoms and related centres -- Vibrational spectra related to hydrogen.
Keywords: Solid state physics; Lasers; Photonics; Optical materials; Electronic materials; Microwaves; Optical engineering; Materials science; Nanotechnology; Solid State Physics; Optics, Lasers, Photonics, Optical Devices; Optical and Electronic Materials; Microwaves, RF and Optical Engineering; Characterization and Evaluation of Materials; Nanotechnology